2013
DOI: 10.1016/j.jpainsymman.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Numbness Modifies the Effect of End-of-Life Discussions on End-of-Life Care

Abstract: Context Overall, end-of-life (EOL) discussions are unrelated to psychological distress and associated with lower rates of aggressive care near death. Nevertheless, patients who report they feel emotionally numb about their illness might encounter difficulties cognitively processing an EOL discussion. Objectives We hypothesized that emotional numbness would modify the influence of EOL discussions on the receipt of less aggressive EOL care. Methods Data were derived from structured interviews with 290 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 18 publications
1
24
0
2
Order By: Relevance
“…29 Increased effort is needed to encourage referring physician participation in some aspect of the consultation or form a strong collaboration with the physician to improve the family experience. 30 Family members' readiness for both attending the family meeting and receiving complete information about the patient's health and disease trajectory was a striking finding from this study. While another palliative care study has documented that some patients felt they received too much information about the patient's condition, 11 the theme of "readiness" has not been well documented in the literature.…”
Section: Discussionmentioning
confidence: 61%
“…29 Increased effort is needed to encourage referring physician participation in some aspect of the consultation or form a strong collaboration with the physician to improve the family experience. 30 Family members' readiness for both attending the family meeting and receiving complete information about the patient's health and disease trajectory was a striking finding from this study. While another palliative care study has documented that some patients felt they received too much information about the patient's condition, 11 the theme of "readiness" has not been well documented in the literature.…”
Section: Discussionmentioning
confidence: 61%
“…One possibility is an individual higher in neuroticism may be more avoidant [2830] of thinking deeply about impending frailty and death when faced with a threatening hypothetical scenario. In “real-world” settings, their avoidance can lead them to refrain from preparing for the future (e.g., not complete advanced directives; not engage in meaningful end-of-life conversation [31, 32]), which could subsequently lead to more intensive service utilization [33]. Alternatively, this avoidance could manifest in more neurotic individuals having lower preferences for both types of end-of-life care simply out of a general desire to be “left alone” when facing significant stressors [8].…”
Section: Discussionmentioning
confidence: 99%
“…6 Many patients are in a state of shock or made emotionally numb by discussion of a terminal prognosis, 7 which may inhibit their ability to comprehend the gravity of their condition. We have reported that among cancer patients with incurable metastatic disease only 38% acknowledged being terminally ill a median of 4 months prior to death.…”
mentioning
confidence: 99%